THE FIRST SCHOOL BOTANICAL GARDEN OF WORLD (PANGEEA, 2025)
The paper presents the history of the Blaj School Botanic Garden, its establishment and development, within the broader international context of creating school botanic gardens. It describes the garden's organization, its flora, and its collaboration with other botanical gardens in the country and abroad to enrich flora and educational practices. It also traces key stages in the garden's evolution, from its origins in the 18th-19th centuries to reforms in the 20th century, highlighting its didactic value as a live laboratory for teaching biology and natural sciences at the secondary school level.
Keywords: botanical garden; plants; plant families; rare plants; natural sciences; biology; forest; greenhouse; shelter; means of education